Monitoring Anti-tuberculosis Treatment Response Using Analysis of Whole Blood Mycobacterium tuberculosis Specific T Cell Activation and Functional Markers - Vickers, Molly A.; Darboe, Fatoumatta; Muefong, Caleb N.; Mbayo, Georgetta; Barry, Amadou; Gindeh, Awa; Njie, Sainabou; Riley, Abi-Janet; Sarr, Binta; Sambou, Basil; Dockrell, Hazel M.; Charalambous, Salome; et al. (Frontiers in Immunology, 2020)
Background: Blood-based biomarkers have been proposed as an alternative to current sputum-based treatment monitoring methods in active tuberculosis (ATB). The aim of this study was to validate previously described phenotypic, activation and cytokine markers of treatment response in a West African cohort. Methods: Whole blood immune responses to Mycobacterium tuberculosis ESAT-6/CFP-10 (EC) and purified protein derivative (PPD) were measured in twenty adults at baseline and after two months of standard TB treatment. Patients were classified as fast or slow responders based on a negative or positive sputum culture result at 2 months respectively. Cellular expression of activation markers (CD38, HLA-DR), memory markers (CD27) and functional intracellular cytokine and proliferation (IFN-γ, Ki-67, TNF-α) markers were measured using multi-colour flow cytometry. Results: There was a significant increase in the proportion of CD4+CD27+ cells expressing CD38 and HLA-DR following EC stimulation at two months compared to baseline (p=0.0328 and p=0.0400 respectively). Following PPD stimulation, slow treatment responders had a significantly higher proportion of CD8+CD27-IFN-γ+ (p=0.0105) and CD4+CD27+HLA-DR+CD38+ (p=0.0077) T cells than fast responders at baseline. ROC analysis of these subsets resulted in 80% sensitivity and 70% and 100% specificity respectively (AUC of 0.82, p=0.0156 and 0.84, p=0.0102). Conclusions: Our pilot data show reductions in expression of T cell activation markers were seen with treatment, but this was not associated with fast or slow sputum conversion at 2 months. However, baseline proportions of activated T cell subsets are potentially predictive of the subsequent speed of response to treatment.